Energy recovery from solid waste valorisation: Environmental and economic potential for developing countries - Petro Karungamye (Scientific African)
Solid waste management in developing countries faces challenges such as rising populations, inadequate planning, poor collection and storage, improper disposal, insufficient technology, and a lack of basic waste management knowledge. Predominantly, waste is disposed of in open dumps, on vacant land, or burned by residents, leading to significant pollution and health risks. Developing countries should adopt solid waste management techniques used by developed nations, with waste-to-energy (WTE) technology being particularly suitable. WTE reduces waste volume and mass, environmental impact, health risks, and reliance on fossil fuels. Fossil fuel exploitation poses severe environmental risks, highlighting the need for secure, sustainable, and renewable energy sources. Biochemical technologies, ideal for high-moisture waste prevalent in developing countries, offer a promising solution. This study examines the potential of WTE valorization in developing countries, evaluating the pros and cons of various WTE conversion technologies and their feasibility. The findings indicate that WTE technologies are underutilized in developing countries. The review suggests that WTE can provide renewable energy, meet energy demands, and improve solid waste management, thereby addressing environmental pollution in developing countries.